Selective use of the mother tongue to enhance students’ english learning processes...beyond the same assumptions (2014)
This article reports the results of an action-research project that examines enhancing students’ English learning processes through the selective use of their mother tongues with the aim of overcoming their reluctant attitudes toward learning English in the classroom. This study involves forty ninth-graders from an all-girls public school in Medellin, Colombia. The data gathered included field notes, questionnaires, and participants’ focus group interviews. The findings show that the mother tongue plays an important role in students’ English learning processes by fostering students’ affective, motivational, cognitive, and attitudinal aspects. Thus, the mother tongue serves as the foothold for further advances in learning English when used selectively.Este artículo presenta los resultados de un proyecto de investigación-acción que examinó el mejoramiento del proceso de aprendizaje de inglés de los estudiantes, a través de un uso selectivo de la lengua materna con el objetivo de superar la actitud reacia hacia el uso del inglés dentro del aula de clase. En este estudio participaron cuarenta estudiantes de noveno grado de un colegio público femenino de la ciudad de Medellín, Colombia. Los datos recogidos incluyen notas de campo, cuestionarios y entrevistas de los participantes a través de grupos focales. Los resultados muestran que la lengua materna juega un papel importante en el proceso de aprendizaje del inglés, al fomentar aspectos afectivos, motivacionales, cognitivos y actitudinales. Así, la lengua materna se sitúa como el punto de apoyo para seguir avanzando en el aprendizaje de inglés, cuando se utiliza de manera selectiva.